Social factors and variation in Language - Omed Barzan Barzo; Umar Ahmad Aziz (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
The research entitled (social factors and variation in Language). The research includes two chapters. The first chapter deals with some theoretical bases and the limits of research. The second chapter deals with variation and the reasons for variation. This research used a descriptive statistics approach. The aim of research is describing important factor of linguistics variation in the Kurdish language, in addition to the presentation of examples varied in multiple social and field events.